1991
DOI: 10.1002/j.1460-2075.1991.tb04986.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronin, an actin binding protein of Dictyostelium discoideum localized to cell surface projections, has sequence similarities to G protein beta subunits.

Abstract: A soluble actin binding protein of Dictyostelium discoideum cells has been extracted and purified from precipitated actin‐myosin complexes. This protein with a relative molecular mass of 55 kDa has been named coronin because of its association with crown‐shaped cell surface projections of growth‐phase D. discoideum cells. In aggregating cells, which respond most sensitively to the chemoattractant cyclic AMP, coronin is accumulated at the front where surface projections are directed towards a cAMP source. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
240
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(250 citation statements)
references
References 49 publications
(22 reference statements)
10
240
0
Order By: Relevance
“…When CF-was substituted by glutamate to approximate physiological conditions (de Hostos et al, 1991), no inhibition of the binding up to 100 mM potassium glutamate was observed; at 75 mM potassium glutamate the binding was even enhanced. An equilibrium binding constant of Dd plastin with F-actin was determined by high-speed centrifugation in the presence of EGTA ( Figure 3C).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…When CF-was substituted by glutamate to approximate physiological conditions (de Hostos et al, 1991), no inhibition of the binding up to 100 mM potassium glutamate was observed; at 75 mM potassium glutamate the binding was even enhanced. An equilibrium binding constant of Dd plastin with F-actin was determined by high-speed centrifugation in the presence of EGTA ( Figure 3C).…”
Section: Resultsmentioning
confidence: 96%
“…Purification of a 67-kDa Protein (p67) from a Contracted Actin-Myosin Complex Contracted actin-myosin complex was prepared from cells starved for 12 h essentially as described previously (Condeelis and Taylor, 1977;Fechheimer and Taylor, 1984;de Hostos et al, 1991). Washed cells were resuspended at 4°C in an equal volume of homogenization buffer [5 mM piperazine-N,N'-bis(2-ethanesulfonic acid) (PIPES), pH 6.8, 5 mM ethylene glycol-bis(,B-aminoethyl ether)-N,N,N',N'-tetraacetic acid (EGTA), 2 mM EDTA, 1 mM phenylmethylsulfonyl fluoride, protease inhibitor cocktail (PIC) consisting of leupeptin, bestatin, pepstatin A, antipain, 10 ,ug/ml each] and disrupted by nitrogen decompression in a Parr bomb (800 psi), followed by gentle agitation with a loose fitting Dounce homogenizer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern and Northern blots were hybridized in the presence of 50% formamide, and Western blots performed after SDS-PAGE of total cellular proteins in 10% gels. The Western blots were labeled using hybridoma 216-394-1 or 176-2-5 [8] culture supernatant and iodinated sheep antimouse IgG (Amersham, Braunschweig, Germany). For quantification of DGAP1 overexpression, antibody 12~I-label on the 95 kDa band of DGAP1 was determined with a Fuji Phosphoimager.…”
Section: Methodsmentioning
confidence: 99%
“…WD repeats typically contain a GH dipeptide 11-24 residues from the N-terminus, and the WD dipeptide at the C-terminus. Proteins with WD repeats have diverse functions, such as signal transduction, RNA processing, transcription, cytoskeleton assembly and mitotic-spindle formation, regulation of vesicle formation and vesicular trafficking, control of various aspects of cell division, and the regulation of sulfur metabolism in fungi [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%